Hubungan antara pola konsumsi protein dan Fe dengan daya tahan jantung paru atlet sepakbola PS Semen Padang tahun 2003 - Kusumawati M; BM Wara Kushartanti; Mochammad Noerhadi (Jurnal Gizi Klinik Indonesia, 2005)
Background: Low cardiorespiratory endurance will decrease the speed and skill in playing soccer. Good cardiorespiratory endurance is important factor in exercise and competition to reach the optimal achievement of the PS. Semen Padang soccer team players. Protein and Fe constitute a supporting factor in forming hemoglobin which is needed for increasing the cardiorespiratory endurance.Objective: This study was aimed at fi nding out the correlation between protein and Fe consumption patterns with the cardiorespiratory endurance of Semen Padang soccer team players in 2003.Methods: This was cross-sectional design of 23 PS. Semen Padang soccer team players. The variables were protein and Fe consumption patterns, hemoglobin concentration and cardiorespiratory endurance. The analysis method was regression Chi-square, multiple linier, and partial correlation.Results: There was no correlation between protein (p=0,683) and Fe (p=0,168) consumption patterns with hemoglobin concentration; there was correlation between hemoglobin concentration with the cardiorespiratory endurance (p=0,022); there was no correlation between protein consumption pattern (p=0,395) with the cardiorespiratory endurance; there was significant correlation between Fe consumption pattern with the cardiorespiratory endurance (p=0,009).Conclusion: Protein and Fe consumption patterns infl uenced the cardiorespiratory endurance athlete PS.Semen Padang through hemoglobin rate cause of hemoglobin rate have signifycant relation with the cardiorespiratory endurance.